Immunomodulatory function of whole human umbilical cord derived mesenchymal stem cells. (July 2017) - Zhang, Hao; Tao, Yanling; Liu, Haihui; Ren, Saisai; Zhang, Bin; Chen, Hu
Highlights: UC-MSCs suppressed T cell proliferation. UC-MSCs modulated the production of inflammatory cytokines by activating T lymphocytes. UC-MSCs modulated the expression of CD8 + T cell subsets. UC-MSCs prevented and lessened aGVHD in allogeneic BMT setting. Abstract: Bone marrow derived mesenchymal stem cells (MSCs) play a critical role in immune modulation. However, immunomodulatory function of whole human umbilical cord derived mesenchymal stem cells (UC-MSCs) remains unclear. In this study, UC-MSCs were separated from whole umbilical cord using a single enzyme digestion. UC-MSCs (CD73 +, CD90 +, CD105 +, and CD34 −, CD45 −, HLA-DR − ) were differentiated into adipocytes, osteocytes and chondrocytes in vitro under specific stimulatory environments. UC-MSCs suppressed umbilical cord blood lymphocyte proliferation stimulated by mitogen, and ELISA showed that the secretion of INF-γ was downregulated, and the secretion of IL-4 was upregulated, with CD8 + T cells markedly decreased and CD4 + T cells changed lightly. Moreover, the infusion of UC-MSCs in recipient mice transplanted with donor bone marrow cells ameliorated acute graft-versus host disease (aGVHD) and extended survival. In conclusion, UC-MSCs might negatively modulate immunoreactions, and have application potential in the treatment of aGVHD caused by allogeneic stem cells transplantation.